Analisa Perbadingan QoS Menggunakan Metode Simple Queue dan Metode Queue Tree pada Hierechical Network Design di Sekolah Dasar Negeri 2 Kelet - Cahyono, Ferdian Bagas; Sulistyo, Wiwin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The development of the internet in human life has had a very positive impact on various fields of life, including the world of education. The education system supported by internet technology has created a distance learning method that can be used by teachers and students in schools. Therefore, the Internet currently plays an important role in supporting the development of the quality of education in Indonesia. The purpose of this study is to produce and then compare the performance of the Queue Tree and Simple Queue Methods using delay, packet loss, and throughput parameters according to the Quality of Service (QoS) parameters. ) SDN Kelet 2. From the results of this study it was found that the Queue Tree Method proved to have better and more stable connection stability because it uses a mangel system to mark each IP. Then the Simple Queue Method also has good connection stability, but it is still inferior to the Queue Tree method because if the client's ping time is full, there will be a packet loss which can cause a lot of wasted bandwidth.